Fabrication, Design and Characterization of Silicon-on-Insulator Waveguide Amplifiers Coated in Erbium-Doped Tellurium Oxide - Naraine, Cameron (My University, 2020)
This research introduces tellurium oxide (TeO2) glass doped with optically active erbium ions (Er3+) as an active oxide cladding material for silicon-on-insulator (SOI) waveguides for realization of a silicon-based erbium-doped waveguide amplifier (EDWA) for integrated optics. Optical amplification of this nature is enabled by energy transitions, such as stimulated absorption and emission, within the shielded 4f shell of the rare-earth atomic structure caused by excitation from photons incident on the system. Er3+ ions are doped into the TeO2 film during deposition onto the SOI waveguides using a reactive magnetron co-sputtering system operated by McMaster’s Centre for Emerging Device Technologies (CEDT). Prior to fabrication, the waveguides are designed using photonic CAD software packages, for optimization of the modal behaviour in the device, and Matlab, for characterization of the optical gain performance through numerical analysis of the rate and propagation equations of the Er3+-based energy system. Post fabrication, the waveguide loss and gain of the coated devices are experimentally measured. The fabricated waveguide amplifier produces a peak signal enhancement of 3.84 dB at 1533 nm wavelength for a 1.7 cm-long waveguide device. High measured waveguide losses (> 10 dB/cm) produce a negative internal net gain per unit length. However, the demonstration and implementation of an active rare-earth doped cladding material on a silicon waveguide is successful, which is a major step in developing integrated optical amplifiers for conventional silicon photonics platforms.
Keywords: photonics; silicon; waveguide; amplifier; rare-earth; integrated optics; silicon photonics; silicon-on-insulator; tellurium oxide; erbium; sputtering